Armed conflict and child mortality in Africa: a geospatial analysis - Wagner, Zachary; Heft-Neal, Sam; Bhutta, Zulfiqar A; Black, Robert E; Burke, Marshall; Bendavid, Eran (The Lancet (British edition), 2018)
A substantial portion of child deaths in Africa take place in countries with recent history of armed conflict and political instability. However, the extent to which armed conflict is an important cause of child mortality, especially in Africa, remains unknown. We matched child survival with proximity to armed conflict using information in the Uppsala Conflict Data Program Georeferenced Events Dataset on the location and intensity of armed conflict from 1995 to 2015 together with the location, timing, and survival of infants younger than 1 year (primary outcome) in 35 African countries. We measured the increase in mortality risk for infants exposed to armed conflicts within 50 km in the year of birth and, to study conflicts' extended health risks, up to 250 km away and 10 years before birth. We also examined the effects of conflicts of varying intensity and chronicity (conflicts lasting several years), and effect heterogeneity by residence and sex of the child. We then estimated the number and portion of deaths of infants younger than 1 year related to conflict. We identified 15 441 armed conflict events that led to 968 444 combat-related deaths and matched these data with 1·99 million births and 133 361 infant deaths (infant mortality of 67 deaths per 1000 births) between 1995 and 2015. A child born within 50 km of an armed conflict had a risk of dying before reaching age 1 year of 5·2 per 1000 births higher than being born in the same region during periods without conflict (95% CI 3·7–6·7; a 7·7% increase above baseline). This increased risk of dying ranged from a 3·0% increase for armed conflicts with one to four deaths to a 26·7% increase for armed conflicts with more than 1000 deaths. We find evidence of increased mortality risk from an armed conflict up to 100 km away, and for 8 years after conflicts, with cumulative increase in infant mortality two to four times higher than the contemporaneous increase. In the entire continent, the number of infant deaths related to conflict from 1995 to 2015 was between 3·2 and 3·6 times the number of direct deaths from armed conflicts. Armed conflict substantially and persistently increases infant mortality in Africa, with effect sizes on a scale with malnutrition and several times greater than existing estimates of the mortality burden of conflict. The toll of conflict on children, who are presumably not combatants, underscores the indirect toll of conflict on civilian populations, and the importance of developing interventions to address child health in areas of conflict. The Doris Duke Charitable Foundation, and the Centre for Global Child Health at the Hospital for Sick Children.